Institutional analysis of multinational corporations' corporate social responsibility policy and practice in Thailand : a case study of Toyota Motor Thailand - Norkaew Senapan (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2012